Upaya Meningkatkan Perilaku Disiplin Siswa Melalui Layanan Bimbingan Kelompok Pada Siswa SMP - Sudewi I Gusti Ayu Agung Krisna; Mulyawan I Nyoman Rajeg (Jurnal Bimbingan dan Konseling Indonesia, 2023)
This research was conducted at SMPN 9 Denpasar in class VII which has low discipline behavior. This counseling guidance action research aims to determine whether Group Guidance Services can improve student discipline behavior. Research data on student discipline behavior was collected using a self-discipline questionnaire and observation results. Data were analyzed using percentage descriptive analysis. The results obtained from this study indicate an increase in student discipline behavior from an initial average of 44% to 63% in cycle I, and to 87% in cycle II. The conclusion that can be drawn from these results is that the application of group guidance services can improve student discipline behavior.